Analysis on Characteristics of Spatial-temporal Precipitation Distribution in Qingyuan Based on Cloud Model - WANG Yan (Renmin Zhujiang)
Based on the traditional Mann-Kendall method,this paper analyzes the spatial-temporal precipitation distribution by the cloud model according to the monthly precipitation data (1990—2020) from 38 stations in Qingyuan City,Guangdong province.The results show that:①In the last 30 years,the precipitation in Qingyuan showed an upward trend in the whole year,flood season and non-flood season,especially in the whole year and flood season.②The stability of precipitation was best in non-flood season,less in whole year,and the worst in flood season.The distribution of precipitation was the most discrete throughout the year,followed by flood season,and more concentrated in non-flood season.③The precipitation showed similar spatial distribution in whole year and flood season,increased from northwest to southeast in general,among them the precipitation in Lianzhou City is small,concentrated and stable.In non-flood season,the distribution of precipitation increased from southeast to northwest,among them the precipitation in the south of Qingcheng District is the least and unstable but concentrated;while that in the northeast of Yingde City is large and stable but not concentrated.